Understanding the ways organizational learning drives information technology (IT) infrastructure - Hassan, N.H.B. (Institute of Electrical and Electronics Engineers Inc., 2014)
Many businesses today are struggling to find a better and substantive IT capability to achieve its competitive advantage. Therefore, this study aims to explore how organizational learning orientation may be the driver that may strengthen organizational IT capability. In the context of this study, organizational learning orientation involves commitment to learning, shared vision, open-mindedness, and intraorganizational knowledge sharing. This study will further explore how these four organization learning orientation may positively or negatively drives organizations' IT capability. Drawing upon dynamic capability theory and Resource-Based View (RBV) theory, four hypotheses are developed to better understand how organizations strategized its IT capability with the right learning orientation. Questionnaires and interviews will be adopted as data collection method and further analyzed with Structural Equation Modeling (SEM). As a result, a validated research model will be empirically validated and presented in the future stages of this research. Â© 2014 IEEE.